2001
DOI: 10.1007/s004020000236
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious effects of local corticosteroid injections on the Achilles tendon of rats

Abstract: The purpose of this study was to examine the pathological changes in the Achilles tendon and its paratenon after intratendinous corticosteroid injections and to reveal the effects of this drug on healthy tendon. We also sought for the effects of these injections compared with compression with a clamp on the Achilles tendons of the rats. Fifty-two Achilles tendons in 26 male Wistar rats were included in the study. Betamethasone injections were applied to the left tendons at different intervals, while the right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…However, there have been many case reports of spontaneous tendon rupture, both after local glucocorticoid injections (Chechick et al 1982, Kleinman and Gross 1983, Stannard and Bucknell 1993, Smith et al 1999) and with systemic glucocorticoid therapy (Kotnis et al 1999). Previous studies on histological and mechanical changes after glucocorticoid injections using in vivo animal models have produced conflicting results (Oxlund et al 1981, Kapetanos 1982, McWhorter et al 1991, Wiggins et al 1995, Campbell et al 1996, Tatari et al 2001. On the other hand, there is little information on the effect of glucocorticoids on tendon at the cellular level.…”
mentioning
confidence: 94%
“…However, there have been many case reports of spontaneous tendon rupture, both after local glucocorticoid injections (Chechick et al 1982, Kleinman and Gross 1983, Stannard and Bucknell 1993, Smith et al 1999) and with systemic glucocorticoid therapy (Kotnis et al 1999). Previous studies on histological and mechanical changes after glucocorticoid injections using in vivo animal models have produced conflicting results (Oxlund et al 1981, Kapetanos 1982, McWhorter et al 1991, Wiggins et al 1995, Campbell et al 1996, Tatari et al 2001. On the other hand, there is little information on the effect of glucocorticoids on tendon at the cellular level.…”
mentioning
confidence: 94%
“…5,6 Evidence from animal studies have shown that glucocorticoids can have deleterious effects on the biomechanical properties of rabbit Achilles tendons, 7 rat peroneal tendons, 8 and rat Achilles tendons. 9 However, as with humans, some studies report a lack of adverse effects. 10,11 These data suggest that the effects of glucocorticoids on tendons is not simple and may depend on a number of variables including choice of drug, dose, site, and method of administration.…”
Section: Introductionmentioning
confidence: 99%
“…with a 22-gauge needle, beginning from the insertion of the tendon to the calcaneus at 3-day intervals for 25 days. This model of degeneration was chosen because recent experimental findings in our study group [16] indicate that tendon and paratenon degeneration can be obtained with local corticosteroid injections.…”
Section: Methodsmentioning
confidence: 99%